2022
DOI: 10.1515/nanoph-2021-0693
|View full text |Cite
|
Sign up to set email alerts
|

Image polaritons in van der Waals crystals

Abstract: Polaritonic modes in low-dimensional materials enable strong light–matter interactions and the manipulation of light on nanometer length scales. Very recently, a new class of polaritons has attracted considerable interest in nanophotonics: image polaritons in van der Waals crystals, manifesting when a polaritonic material is in close proximity to a highly conductive metal, so that the polaritonic mode couples with its mirror image. Image modes constitute an appealing nanophotonic platform, providing an unparal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 112 publications
0
20
0
Order By: Relevance
“…A series of recent experimental works highlighted a new species of low-dimensional polaritons supported by the van der Waals crystals placed in proximity to a highly conductive metal-the image polaritons (16), resulting from the coupling of the collective charge oscillation in the polaritonic material with their images in the metal (5,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Because of the lack of geometry-driven cutoff, image modes have been demonstrated to provide an unexcelled degree of field confinement into the nanometer-scale volumes (22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…A series of recent experimental works highlighted a new species of low-dimensional polaritons supported by the van der Waals crystals placed in proximity to a highly conductive metal-the image polaritons (16), resulting from the coupling of the collective charge oscillation in the polaritonic material with their images in the metal (5,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Because of the lack of geometry-driven cutoff, image modes have been demonstrated to provide an unexcelled degree of field confinement into the nanometer-scale volumes (22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…We also plotted the light line in free space for comparison as shown in Figure 3a. Moreover, the FOM of HIGP is twice higher than that of HGP at f > 3 THz as shown in Figure 3b, indicating that HIGP possesses two times higher normalized propagation length L np = L p /λ pl [ 52,55 ] than that of HGP, where L p = λ/[4πIm( n e )] is the practical propagation length of plasmon waves. As f increases, the difference in Re( q ) between HGP and HIGP increases because n Au decreases as f increases around the THz regime, leading to more HIGP fields penetrating into the Au substrate.…”
Section: Comparison Of Higp and Hgpmentioning
confidence: 99%
“…Previous studies, such as, the references [ 47–55 ] have reported the guiding mechanism of IGP. However, the mode analyses are limited to only one‐dimensional layered configuration.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, when a polaritonic van der Waals crystal is placed in proximity to a metal, the coupling between the collective charge oscillations and their images in the metal results in a manifestation of a new low‐dimensional mode—the “image polariton”. [ 22,23 ] Image polaritons have an overarching advantage: significantly stronger field confinement, yet similar lifetime compared to their counterparts in the same material on a low‐loss dielectric substrate. [ 24 ] This unique dispersion property stems from the smaller group velocity while the material loss practically does not change, and manifests in a longer normalized propagation length in optical cycles.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] At the same time, when a polaritonic van der Waals crystal is placed in proximity to a metal, the coupling between the collective charge oscillations and their images in the metal results in a manifestation of a new low-dimensional mode-the "image polariton". [22,23] Image polaritons have an overarching Orthorhombic molybdenum trioxide (α-MoO 3 ), a newly discovered polaritonic van der Waals crystal, is attracting significant attention due to its strongly anisotropic mid-infrared phonon-polaritons. At the same time, coupling of polariton with its mirror image in an adjacent metal gives rise to a significantly more confined image mode.…”
mentioning
confidence: 99%